Основні положення досудового порядку врегулювання спору в судовому процесі - Кройтор, В. А.; Kroitor, V. A.; ORCID: http://orcid.org/0000-0002-1849-5721 (Право і суспільство. - 2020. - № 2, ч. 1. - С. 195-200, 2020)
Проаналізовано сутність інституту досудового порядку врегулювання спору в судовому процесі. Констатовано, що можливість звернення особи до сторони, яка є порушником прав, свобод чи інтересів, з метою вирішити претензії, що виникли у неї до кредитора, і становить найголовніше значення обов’язкового досудового врегулювання спорів. Вирішуючи таким чином спір, позивач охороняє й інтереси відповідача. Отже, якщо вони внаслідок обов’язкового досудового врегулювання у добровільному порядку вирішать розбіжності, то відповідача буде позбавлено непередбачених додаткових судових витрат – у разі, якщо спір буде передано на розгляд суду.

The author of the article has analyzed the essence of the institution of pre-trial dispute resolution within court proceedings. In particular, the author has noted that the norms of the Commercial Procedural Code of Ukraine, the Civil Procedural Code of Ukraine and the Code of Administrative Proceedings of Ukraine regarding the determination of the procedure for pre-trial dispute resolution within court proceedings were adopted in compliance with the provision of the Constitution of Ukraine, contained in Part 3 of the Art. 124 – “the law may determine the mandatory pre-trial procedure for dispute resolution”. The author considers it possible to positively evaluate these changes, but according to the author, the instruction for pre-trial disputes resolution, in this case, which the legislator enshrined in the Constitution of Ukraine, is insufficient to resolve the conflict, but there is the need to further elaborate this provision in order to create an effective dispute resolution mechanism. Such mechanisms have long been successful and sufficiently effective in Western legal systems. Consolidation of the possibility of taking measures to settle a dispute at the law level before going to court, should be considered as an important element in the legal regulation of relations of individuals and legal entities, the state. The author of the paper has stated that the possibility to address the party who is an offender and violated the rights, freedoms or interests in order to resolve the claims that have arisen against a creditor, and is of paramount importance to a mandatory pre-trial dispute resolution. At the same time, resolving the dispute in this manner, the plaintiff also protects the defendant’s interests. Therefore, if they resolve the dispute by a mandatory pre-trial settlement on a voluntary basis, then the defendant will be deprived of unforeseen additional court costs – if the dispute is referred to the court.

Проанализирована сущность института досудебного порядка урегулирования спора в судебном процессе. Констатировано, что возможность обращения лица к стороне, являющейся нарушителем прав, свобод или интересов, с целью разрешить возникшие у нее к кредитору претензии и составляет самое главное значение обязательного досудебного урегулирования споров. Разрешая таким образом спор, истец охраняет и интересы ответчика. Следовательно, если они в результате обязательного досудебного урегулирования в добровольном порядке разрешат разногласия, то ответчик будет лишен непредвиденных дополнительных судебных расходов – в случае, если спор будет передан на рассмотрение суда.
Main provisions of pre-trial procedure of dispute resolution within court proceedings
Кройтор, В. А. Основні положення досудового порядку врегулювання спору в судовому процесі / Кройтор В. А. // Право і суспільство. - 2020. - № 2, ч. 1. - С. 195-200. - DOI: https://doi.org/10.32842/2078-3736/2020.2-1.31.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; досудовий порядок врегулювання спору; pre-trial dispute settlement procedure; досудебный порядок урегулирования спора; претензійний порядок врегулювання спору; pretentious dispute settlement procedure; претенциозный порядок урегулирования спора; альтернативне вирішення спору; alternative dispute resolution; альтернативное разрешение спора; адміністративне судочинство; administrative proceedings; административное судопроизводство; господарський процес; economic process; хозяйственный процесс